Risk factors of pyometra in cat at several clinics in Kediri, East Java, Indonesia - Rosyta, Pegy; Rimayanti Rimayanti; Budi Utomo; Jola Rahmahani; Yulianna Puspitasari; Wiwik Misaco Yuniarti (Universitas Airlangga, 2024)
Pyometra is a reproductive disease that most often affects cats which is caused by bacterial infection of the uterus. This study aims to determine the risk factors that could influence the occurrence of pyometra in cats. The study was conducted at the Four Leg Pet Care, Asa Animal Clinic, and K-5 Animal Care in Kediri regency in December 2021 to February 2022. This retrospective cohort study took secondary data for the period 2020 to 2021 as research material and found 35 cats diagnosed with pyometra. The odds ratio was calculated to analyze the associations to some factors including age, body weight, use of hormonal contraception, frequency of administration of hormonal contraception, hormonal contraceptive drugs used, dose of hormonal contraception given. Analysis of the relationship between risk factors for pyometra showed that the factors age, use of hormonal contraception, and frequency of giving hormonal contraceptives each have p values ​​of 2.17, 2.13, and 2.13, respectively. It could be concluded that age, use of hormonal contraception, and frequency of administration of hormonal contraception influenced or had an association with the risk of pyometra in cats.